Very low calorie ketogenic diet combined with physical interval training for preserving muscle mass during weight loss in sarcopenic obesity: A pilot study - Camajani, Elisabetta; Feraco, Alessandra; Proietti, Stefania; Basciani, Sabrina; Barrea, Luigi; Armani, Andrea; Lombardo, Mauro; Gnessi, Lucio; Caprio, Massimiliano (Frontiers in Nutrition, 2022)
Background The prevalence of sarcopenic obesity (SO) is increasing worldwide, posing important challenges to public health and national health care system, especially during the COVID pandemic. In subjects with SO, it is essential to reduce body weight, and to preserve lean mass, to avoid worsening of muscle function. Adequate nutrition and correct physical activity is essential to counteract SO progression. Very Low Calorie Ketogenic Diet (VLCKD), a well-established nutritional intervention for obesity, has been also indicated for the treatment of SO. To date, the effects of physical training during VLCKD have not been investigated. Aim This pilot study aims to determine the efficacy of VLCKD combined with interval training, compared to a VLCKD alone, on weight-loss, body composition, and physical performance in participants with SO. Materials and methods Twenty-four participants with SO, aged between 50 and 70 years, who met the inclusion criteria, accepted to adhere to a VLCKD (<800 Kcal/die) and to give informed consent, were enrolled in the study. Twelve participants followed a structured VLCKD protocol (VLCKD group) and twelve followed the same VLCKD protocol combined with interval training (IT), twice per week (VLCKD + IT group). Data were collected at baseline (T0) and after 6-week of treatment (T6). Anthropometric indexes, body composition analysis by Bioelectrical Impedance Analysis (BIA), muscle strength and physical performance analysis were assessed at baseline and at the end of treatment. Results At the end of the study, body mass index (BMI), body weight, waist circumference, and hip circumference were significantly reduced in both VLCKD group and VLCKD + IT group. Interestingly, a significant improvement in muscle strength and physical performance was observed in both groups. A multiple comparison of delta variations in all parameters between groups was performed. No differences were observed for the majority of anthropometric and biochemical parameters, with the exception of fat free mass (FFM) and fat mass (FM): notably, participants who followed a VLCKD combined with IT preserved FFM (p < 0.001) and reduced FM (p = 0.001) to a greater extent than what observed in VLCKD group. Moreover, high density lipoprotein (HDL) cholesterol plasma levels were significantly higher in the VLCKD + IT group compared to the VLCKD group. Conclusion This pilot study confirms that VLCKD is effective in terms of body weight reduction, particularly FM; moreover, the combination of VLCKD and interval training could determine a better preservation of FFM.